تأثير تغير نسبة التسليح الهجين (فولاذ - كربون СFRP) على سلوك الجوائز البيتونية المسلحة المعرضة للانحناء - غاندي علي جحجاح; أحمد علي عبود; ميرفت حسن حشمة (Tishreen University, 2014)
يعتبر تسليح العناصر البيتونية تسليحاً مشتركاً(هجيناً ) بقضبان فولاذية و كربونية СFRPأمراً واعداً ومفيداً  نظراً لما يحققه هذا التسليح المشترك من قوة و قابلية للتشغيلبالإضافة للمتانة العالية والديمومة،وذلك في حال الاستعاضة عن قضبان التسليح الفولاذية في زوايا مقاطع العناصر بقضبان كربونية لا تصدأ وذات مقاومة عالية. قمنا بدراسة تجريبية على جوائز بيتونية متماثلة ومسلحة بقضبان فولاذية أو كربونية، أو بشكل هجين بقضبان فولاذية وكربونية معاً، وذلكلإثبات مدى فاعلية تسليح العناصر البيتونية بهذهالأنواعالمختلفة من التسليح و لمقارنة سلوكها.جرت عملية الاختبار على 12 جائزاً مقسمة إلى أربع مجموعات في كل منها ثلاثة جوائز وكان المتغير الأساسي هو نسبة التسليح بالكربون إلى نسبة التسليحالكلية.وأبدت الجوائز المسلحة بقضبان كربونية قدرات تحمل أعلى بالمقارنة مع الجوائز الأخرى, كما ازدادت قدرات التحمل في الجوائز المسلحة بشكل هجين وفق النسب التالية:(0-10-15-22)%، عندازدياد نسبة التسليح بالكربون في مقطعهاإلى نسبة التسليحالكلية وفق النسب(0-33.3-66.6-100)% بالتتالي. Reinforcing concrete elements with a combination (hybrid) of steel and carbon CFRP bars is considered promising in terms of strength, serviceability, and durability, especially in the case of replacing steel bars in the corners of the element-sections  by carbon rods which don't rust and have a high strength. To prove the effectiveness of reinforcing concrete elements with different types of reinforcement, and to compare the behavior of these elements, we have experimentally investigated the behavior of uniform concrete beams reinforced with either steel or carbon bars or steel and carbon together (hybrid reinforcement). 12 beams were divided into four groups each; three beams were tested. The amount of CFRP reinforcement and the CFRP ratio of the total reinforcement were the main parameters investigated. Concrete beams reinforced with carbon rods exhibited a higher load carrying capacity compared with other beams. Also, the load carrying capacity increased in the concrete beams reinforced with hybrid reinforcement, according to the following rates (0-10-15-22)%, by increasing the CFRP ratio of the total reinforcement in their sections, according to the following rates (0-33.3-66.6-100%), respectively.